Unlocking the transcriptomes of two carcinogenic parasites, Clonorchis sinensis and Opisthorchis viverrini. - Neil D Young; Bronwyn E Campbell; Ross S Hall; Aaron R Jex; Cinzia Cantacessi; Thewarach Laha; Woon-Mok Sohn; Banchob Sripa; Alex Loukas; Paul J Brindley; Robin B Gasser (Public Library of Science (PLoS), 2010)
The two parasitic trematodes, Clonorchis sinensis and Opisthorchis viverrini, have a major impact on the health of tens of millions of humans throughout Asia. The greatest impact is through the malignant cancer ( = cholangiocarcinoma) that these parasites induce in chronically infected people. Therefore, both C. sinensis and O. viverrini have been classified by the World Health Organization (WHO) as Group 1 carcinogens. Despite their impact, little is known about these parasites and their interplay with the host at the molecular level. Recent advances in genomics and bioinformatics provide unique opportunities to gain improved insights into the biology of parasites as well as their relationships with their hosts at the molecular level. The present study elucidates the transcriptomes of C. sinensis and O. viverrini using a platform based on next-generation (high throughput) sequencing and advanced in silico analyses. From 500,000 sequences, >50,000 sequences were assembled for each species and categorized as biologically relevant based on homology searches, gene ontology and/or pathway mapping. The results of the present study could assist in defining molecules that are essential for the development, reproduction and survival of liver flukes and/or that are linked to the development of cholangiocarcinoma. This study also lays a foundation for future genomic and proteomic research of C. sinensis and O. viverrini and the cancers that they are known to induce, as well as novel intervention strategies.